EKSISTENSI DAN PEWARISAN SILAT PISAU DI KABUPATEN KEPULAUAN ANAMBAS - Mubarok, Jauhar; Buduroh, Mamlahatun; Sari, Renny Puspa (Multikultura, 2025)
Silat Pisau is a distinctive cultural heritage of the Anambas Islands Regency. Although it has existed for quite some time, its presence has remained relatively obscure—possibly due to its exclusion from modern silat organizations. Silat Pisau began to develop several years before Indonesia’s independence in the village of Candi, Anambas Islands Regency, with the knife serving as the primary weapon in its practice. The use of this weapon carries both practical and philosophical significance. This paper aims to provide an overview of the existence and transmission of Silat Pisau in the Anambas Islands Regency. A qualitative approach was employed in this study, utilizing literature review, observation, and interviews. Analysis of the movements and the tradition of inheritance reveals that the knife is used primarily due to its accessibility; it can be found easily in nearly every household. Its relatively small size and shape also make it convenient to carry. Furthermore, the transmission of this tradition contains symbols or signs that can be interpreted as moral guidelines for personal conduct and social interaction.